Potensi Bakteri Simbion Rayap sebagai Agens Pengendali Hayati Penyakit Rebah Semai (Sclerotium rolfsii) pada Tanaman Kedelai secara In Vitro: Potential of Termite Symbiotic Bacteria as Biological Control Agents for Seedling Damping-Off Disease (Sclerotium Rolfsii) in Soybean Plants In Vitro - Sakti, Vernanda Hani Pradana; Widura, Ardeva Duta; Maulana, Achmad Diva; Wiya, Zattury Alda; Rofiqoh, Risma Azizatur; Alif, Trisnani; Dinata, Gallyndra Fatkhu (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
Termite symbiotic bacteria have potential as a biological agent that has not been extensively researched. This research aims to uncover the potential of termite symbiotic bacteria as a biological agent against the damping off disease (Sclerotium rolfsii) in soybean plants. The research was conducted in the plant protection laboratory, biosciences laboratory, and innovation garden of Jember State Polytechnic over 4 months. The study was designed based on a Completely Randomized Design (CRD) with 6 treatments, each repeated 4 times. The treatments included: P1 pathogenic fungus as control, P2-P4 pathogen with termite symbiotic bacteria with the highest inhibition percentage, and P6 pathogen S. rolfsii. The stages of the research began with the Isolation of Termite Symbiotic Bacteria, Antagonistic Screening Test, Hypersensitivity Test, and In Vitro Antagonistic Test. From the results of testing four isolates, the ability to inhibit the pathogen S. rolfsii was observed. These isolates are IR1A1, IR1A4, IR1A6, and IR4D2. The effectiveness of inhibiting S. rolfsii ranged from 28.97% to 95.79% in vitro. The most effective bacterial isolate in suppressing the pathogen and capable of surpassing fungicide treatment is isolated IR1A6, which has an inhibition rate of up to 95.79%.